Heart Rate Variability: Why Chaos can be healthy - Jorge Cancino (Pensar en Movimiento)
Body autonomic interactions, mediated by sympathetic-parasympathetic balance, have been widely associated with stress and internal homeostasis. The acquisition of data, otherwise hidden in the signal from RR interval duration in heart rate, has given scientists access to the quantification of autonomic balance in humans, as long as the appropriate mathematical analyses are performed. With this information it is possible to know and understand the chaotic behavior of RR signals; this behavior shows the existence of heart rate variability (HRV). Variability is lost in some conditions associated with the presence of pathologies. In addition, with exercise being a stress agent, HRV analysis has been used as a tool to study training load assimilation and overtraining syndrome.